Identification of Antidiabetic Compounds from the Aqueous Extract of Sclerocarya birrea Leaves - Vinesh Maharaj; Chidinma Christiana Ezeofor; Dashnie Naidoo Maharaj; Christo J. F. Muller; Nnini Jennifer Obonye (Molecules, 2022)
Diabetes, a prevalent metabolic condition with a wide range of complications, is fast becoming a global health crisis. Herbal medicine and enhanced extracts are some of the therapeutic options used in the management of diabetes mellitus. The plant-derived molecules and their suitable structure modification have given many leads or drugs to the world such as metformin used as an antidiabetic drug. The stem extract of Sclerocarya birrea has been reported as a potent antidiabetic (glucose uptake) agent. However, the bioactive compounds have not been reported from S. birrea for treatment of diabetes. In this study, the spray-dried aqueous leaf extracts of S. birrea were investigated as an antidiabetic agent using a 2-deoxy-glucose (2DG) technique showing good stimulatory effect on glucose uptake in differentiated C2C12 myocytes with % 2DG uptake ranging from 110–180% that was comparable to the positive control insulin. Three compounds were isolated and identified using bioassay-guided fractionation of the spray-dried aqueous extract of S. birrea leaves: myricetin (1), myricetin-3-O-β-D-glucuronide (2) and quercetin-3-O-β-D-glucuronide (3). Their chemical structures were determined using NMR and mass spectrometric analyses, as well as a comparison of experimentally obtained data to those reported in the literature. The isolated compounds (1–3) were studied for their stimulatory actions on glucose uptake in differentiated C2C12 myocytes. The three compounds (1, 2 and 3) showed stimulatory effects on the uptake of 2DG in C2C12 myocytes with % 2DG uptake ranging from 43.9–109.1% that was better compared to the positive control insulin. Additionally, this is the first report of the flavonoid glycosides (myricetin-3-O-β-D-glucuronide) for antidiabetic activity and they are the main bioactive compound in the extract responsible for the antidiabetic activity. This result suggests that the S. birrea leaves have the potential to be developed for treatment of diabetes.